O Piano Complementar e a Interdisciplinaridade: performance, apreciação e criação integradas na formação acadêmica do bacharelado e da licenciatura - Maria Inez Lucas Machado (2008)
This study establishes the basis for an interdisciplinary approach of Secondary Piano, which could promote integration between diverse fields of the academic formation at undergraduate level, both in the Bachelor of Music and Teaching Certification degrees. Themes like teaching, musical development, pre-college musical learning and the pedagogic integration between appreciation, performance and composition, are discussed and contextualized. In the same way, some thinkers ideas regarding art making are approached and directly related to the practice and reflection about music and music education. The active observation of the performance by students and the study of the opinions and data from students and teachers of the Federal University of Minas Gerais School of Music, as well as teachers from two different music colleges, provided foundations for the considerations and pedagogical propositions presented.